2021
DOI: 10.1111/cch.12838
|View full text |Cite
|
Sign up to set email alerts
|

Supporting families of children with an undiagnosed genetic condition: Using co‐design to ensure the right person is in the right post doing the right job

Abstract: Background Families and professionals caring for a child without a definitive diagnosis face unique challenges, particularly in relation to managing uncertainty; access to healthcare; obtaining relevant information and support; and trying to navigate a healthcare system that is often fragmented. We used co‐design to inform the establishment of the first UK specialist nursing post dedicated to working with children with undiagnosed genetic conditions and their families. Objectives: (1) To understand what famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In line with previous research (Oulton et al , 2021), service provider skills were found to be vital to the success of the FLS, however participants reported that being independent from health and social care is a clear strength and increased families’ confidence in a FLO providing impartial, accessible and practicable advice. FLOs who are able to draw on their own personal experience of disability within the family was considered invaluable.…”
Section: Discussionsupporting
confidence: 85%
“…In line with previous research (Oulton et al , 2021), service provider skills were found to be vital to the success of the FLS, however participants reported that being independent from health and social care is a clear strength and increased families’ confidence in a FLO providing impartial, accessible and practicable advice. FLOs who are able to draw on their own personal experience of disability within the family was considered invaluable.…”
Section: Discussionsupporting
confidence: 85%
“…These findings are the focus of this paper. The use of co-design with key stakeholders, including families, to influence the nature of the role and how it was implemented in practice has been described elsewhere (Oulton et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Familycentered care also recognizes and integrates the important role of families in pediatric health care, ensuring parent-professional collaboration, information sharing, and family-support (Kokorelias, Gignac, Naglie, & Cameron, 2019). In the United Kingdom (UK), research has found that families of children with an undiagnosed condition have described health as requiring improvements to care-coordination, awareness, and advocacy, and that parents are emotionally impacted while managing uncertainty (Aldiss et al, 2021;Oulton et al, 2021). Similarly, research globally has identified that access to health services and information provision could be improved (Brannon, Ray, Lark, & Kindratt, 2021;Kiernan, Courtney, Ryan, McQuillan, & Guerin, 2020).…”
mentioning
confidence: 99%